1985
DOI: 10.1093/nar/13.18.6483
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequences from pbaseolln cDNA clones: the major storage proteins fromPhaseolus vulgarisare encoded by two unique gene families

Abstract: The nucleotide sequences of eight partial and five full-length phaseolin cDNA clones show that phaseolin polypeptides are encoded by two distinct gene families which differ in their coding regions by the presence or absence of two different size direct repeats. The alpha-type phaseolin polypeptides are encoded by genes containing direct repeats which encode 14 additional amino acids. Aside from these differences, the alpha-and beta-type phaseolin genes show a high degree of homology (98%) which is consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0
3

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 42 publications
5
70
0
3
Order By: Relevance
“…After prolonged exposure, minor products could also be detected which initiated at Ϫ9, ϩ4, and ϩ16/ϩ17. These findings are consistent with previous mapping studies in bean cotyledons which identified a complex pattern of phas messages predicted to originate between Ϫ12 and ϩ5, with the predominant forms localizing around ϩ1 and Ϫ11 (21). Substitution of hTBP with purified recombinant wheat TBP (a gift of S. Ackerman, University of Massachusetts) (32) had no effect on the location of transcription initiation, although the preference for ϩ1 was slightly enhanced.…”
Section: Reconstitution Of Phas Transcription In Vitro-supporting
confidence: 91%
See 3 more Smart Citations
“…After prolonged exposure, minor products could also be detected which initiated at Ϫ9, ϩ4, and ϩ16/ϩ17. These findings are consistent with previous mapping studies in bean cotyledons which identified a complex pattern of phas messages predicted to originate between Ϫ12 and ϩ5, with the predominant forms localizing around ϩ1 and Ϫ11 (21). Substitution of hTBP with purified recombinant wheat TBP (a gift of S. Ackerman, University of Massachusetts) (32) had no effect on the location of transcription initiation, although the preference for ϩ1 was slightly enhanced.…”
Section: Reconstitution Of Phas Transcription In Vitro-supporting
confidence: 91%
“…In vitro and in vivo analysis of phas promoter activity demonstrated that the TATA box elements are required for basal transcription. Mapping of the primary and secondary phas transcription start sites confirmed that the HeLa in vitro transcription system accurately reconstituted the in vivo pattern of phas transcription initiation (21). The reconstitution of phas basal transcription regulation on naked DNA templates indicates that the observed requirement for core promoter organization is chromatin-independent.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Both enzymes combine in an unusual pathway, not known to exist in higher plants, to produce indole-3-acetic acid whereby iaaM is the rate-limiting enzyme (2-4). Seed-specific expression is mediated by the embryo-specific phaseolin promoter from French bean, Phaseolus vulgaris (5). Repression of the SL construct is conferred by the R element tetR that acts on Fig.…”
mentioning
confidence: 99%